COMPARISON OF PERIOD VALUE, DISPLACEMENT, AND DEVIATION BETWEEN LEVELS IN EKA CANDRARINI HOSPITAL BUILDING USING FIXED BASE SYSTEM AND BASE ISOLATION SYSTEM (HDRB) - Nanda Primarta Nadila; Wahyu Kartini; Sumaidi (LPPM Universitas Abdurrab, 2025)
One of the innovations that continues to be developed in the planning of earthquake-resistant building structures is the use of base isolation systems. Base isolation has various types, one of which is high damping rubber bearing (HDRB). HDRB is one type of base isolation that has a relatively large initial stiffness value, so can reduce a high enough earthquake force. To find out the comparison of period, displacement, and deviation values between levels using a fixed base system and an HDRB type base isolation system in the Eka Candrarini Hospital building, it is necessary to calculate the structural analysis using an auxiliary program. Based on the analysis, it was found that there was an increase in the period value of the structure by 67%, the displacement value in the X direction by 73% and the Y direction by 22%, and a decrease in the deviation value between levels by 42% in the X direction and 43% in the Y direction.